Impact evaluation of scripted lesson plans for HIV-related content in a life orientation curriculum: results from two provinces in South Africa - Ilene S. Speizer; Mahua Mandal; Khou Xiong; Ndinda Makina; Aiko Hattori; Darryn Durno (BMC, 2020)
Abstract Background Young people under age 25 years are a key population at risk of unintended pregnancies, HIV and other sexually transmitted infections. School-based programming, focusing on youth under 17 years is strategic given that many in this age group are in school or are required to be in school and spend a considerable amount of their time at school. Prior evaluations of school-based HIV prevention programs for young people often employed weak study designs or lacked biomarkers (e.g., HIV or STI testing) to inform outcomes. Methods This study used longitudinal data collected in 2016 from a cohort of grade-8 girls from Mpumalanga and KwaZulu-Natal Provinces in South Africa. We followed them for 2 years to examine the impact of the South African Department of Basic Education's revised scripted lesson plans for the HIV and sexual content of a "life orientation" curriculum on knowledge, attitudes, condom use behaviors, pregnancy incidence, and genital herpes incidence. Schools were randomized to intervention and control arms. Multivariable analyses were undertaken using hazard modeling for incidence-based outcomes (genital herpes and pregnancy) and generalized linear latent and mixed modeling for outcomes measured at each time period (knowledge, attitudes, and condom use). Results At end line, 105 schools were included from the two provinces (44 from Mpumalanga and 61 from KwaZulu-Natal). Fifty-five were intervention and fifty were control schools. A total of 2802 girls were surveyed at both time periods (1477 intervention and 1325 control). At baseline, participating girls were about 13.6 years; by end line, they were about 2 years older. Longitudinal data demonstrated few differences between intervention and control groups on knowledge, attitudes, condom use, genital herpes, and pregnancy experience. Monitoring data demonstrated that the program was not implemented as intended. Our results demonstrated 7% incidence of genital herpes in the two-year follow-up period indicating sexual risk-taking among our cohort. Conclusions We did not find significant effects of the revised life orientation curriculum on key outcomes; however, this may reflect poor implementation. Future HIV prevention programs for young people need to be implemented with fidelity to ensure they meet the crucial needs of the next generation. Trial Registration: This study has been registered at ClinicalTrials.gov . The trial registration number is: NCT04205721 . The trial was retrospectively registered on December 18, 2019.